ENVIRONMENTAL POTENTIAL OF HIGHER EDUCATION, IN PARTICULAR OF HIGHER TECHNICAL SCHOOL - Саєнко, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The information society has accelerated socio-economic processes, technological cycles are not 20-30 years, but only 3-5, which radically changes the tasks of professional training of personnel at all levels and specialties. The problem of environmental education went beyond the national framework and gained international significance. The HDI (human development index) in Ukraine occupies a more or less worthy place among other countries due to the high rating of the educational component. National pedagogy should more actively introduce scientific developments and achievements into educational practice, in particular, through new special courses, technologies of formation of ecological thinking, consciousness, culture of high schools students, using modern psychological and pedagogical approaches